Harmonisasi Regulasi Insentif Penanaman Modal Kabupaten Sidoarjo Pasca Berlakunya Undang-undang Nomor 6 Tahun 2023 Tentang Cipta Kerja - Swastika Maya Pramesti; Muhammad Asrul Maulana; Ni Ketut Indhira Maharani (Jayapangus Press, 2026)
The background of this research is to examine and analyze the legitimacy of the Regional Government in regulating investment incentives and facilities based on the principles of legality and hierarchy of laws and regulations, analyzing the suitability of the practice of providing investment incentives and facilities in Sidoarjo with the basic principles of investment, including the principle of non-discrimination, international obligations, and compliance with national law. The purpose of this research is to formulate more integrated policy recommendations between the central and regional governments in order to create a more inclusive fiscal policy system in terms of investment. This research method uses a normative approach with a statute approach and a conceptual approach. The results of this study show that Sidoarjo Regency Regional Regulation Number 5 of 2014 and Regent Regulation Number 58 of 2015 have become the basis for providing incentives do not fully reflect the basic principles of investment stated in the latest national laws such as Law Number 6 of 2023 concerning Job Creation, and have not been integrated with Indonesia's international obligations in global investment agreements. This inconsistency creates the risk of legal uncertainty and has the potential to reduce investor confidence, both domestic and foreign. The conclusion of this research is that legal protection is needed for investors related to incentives through reporting, evaluation, guidance and supervision mechanisms, as well as government incentive products that can be utilized by investors.